Participation of Health Facility Governing Committees in Budget and Plan Review and Approval at Lower Health Facility: Experiences from Kigoma Region Tanzania (Universitas PGRI Madiun, 2023)
For the purpose of involving communities in primary healthcare, health facility governing committees (HFGCs) were created. This study focused on meeting frequency, feedback techniques, and difficulties to better understand how HFGCs evaluate and approve plans and budgets. A cross-sectional survey was done with 75 HFGC members from 9 sites. The majority of HFGCs (82.6%) met quarterly to improve the delivery of health services, according to descriptive analysis performed using SPSS 20. Common means of getting comments were notice boards (49.4%), village assembly (94.7%), and unofficial gatherings (69.3%). Misunderstandings (78.7%), power dynamics (61.4%), a lack of financing (81.4%), political interference (60%) and knowledge deficits were among the difficulties. Planning and budgeting were enhanced by effective HFGCs with frequent meetings and feedback systems, which in turn improved healthcare delivery